Botswana : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
In response to a request for IMF technical assistance (TA) made by the Botswana authorities and in consultation with the IMF's African Department, a government finance statistics (GFS) TA mission from the IMF's Statistics Department visited Gaborone during the period March 13-24, 2017. The mission is part of the GFS Module of the United Kingdom's Department for International Development-funded Enhanced Data Dissemination Initiative 2. The main objective of the mission was to continue to assist the Ministry of Finance and Economic Development (MFED) in the compilation and dissemination of fiscal statistics in accordance with the guidelines of the Government Finance Statistics Manual 2014 (GFSM 2014) and Public Sector Debt Statistics: Guide for Compilers and Users.